The tale of the Princess Kaguya [videorecording (DVD)] - Takahata, Isao (Studio Ghibli, 2015)
Found inside a shining stalk of bamboo an old bamboo cutter and his wife, a tiny girl grows rapidly into an exquisite young lady. The mysterious young princess enthralls all who encounter her, but ultimately she must confront her fate, the punishment for her crime.